Didactic Opportunities in Mastering Lessons for Elementary School Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Learning is a two-way process. It includes teaching - the activity of a teacher who directs the processes of perception, understanding and memorization by students of educational material, and learning - the activity of students who perceive educational material, comprehend and remember it, learn to apply acquired knowledge in practice.